2021
DOI: 10.1016/j.lanwpc.2021.100172
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining cancer services during the COVID-19 pandemic: the Aotearoa New Zealand experience

Abstract: COVID-19 caused significant disruption to cancer services around the world. The health system in Aotearoa New Zealand has fared better than many other regions, with the country being successful, so far, in avoiding sustained community transmission. However, there was a significant initial disruption to services across the cancer continuum, resulting in a decrease in the number of new diagnoses of cancer in March and April 2020.Te Aho o Te Kahu, Aotearoa New Zealand's national Cancer Control Agency, coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Some countries will experience a greater impact of COVID-19, particularly those with a high prevalence of SARS-CoV-2 infection and those with poorer healthcare infrastructure/oncology management systems. Oncology services in countries with virtual elimination of the virus were able to quickly resume/catch-up following lockdown periods [ 17 ], whereas recovery in other countries will be an extremely long process. It is important that individual countries report data regarding changes to oncology management so that responses to the current pandemic can be adapted and improved, and lessons learned in the event of a future pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Some countries will experience a greater impact of COVID-19, particularly those with a high prevalence of SARS-CoV-2 infection and those with poorer healthcare infrastructure/oncology management systems. Oncology services in countries with virtual elimination of the virus were able to quickly resume/catch-up following lockdown periods [ 17 ], whereas recovery in other countries will be an extremely long process. It is important that individual countries report data regarding changes to oncology management so that responses to the current pandemic can be adapted and improved, and lessons learned in the event of a future pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other regions, the arrival of COVID-19 and the national lockdown in New Zealand during 2020 created disruptions and additional barriers to accessing health care in general, and in particular presented a risk to cancer diagnosis, treatment, and the continuation of care. 26,27 Te Aho o Te Kahu worked to ensure that actions (particularly emergency actions) taken within the health system did not result in the further exacerbation of existing inequities. For example, the agency engaged on a daily basis with Hei Āhuru Mōwai worked closely with clinical colleagues around the country, generated evidence-based guidance that specifically addressed pathways through which inequity could occur, 27 and then regularly monitored differences.…”
Section: Panel 2: Providing Equity-focused Cancer Control Guidance Du...mentioning
confidence: 99%
“…26,27 Te Aho o Te Kahu worked to ensure that actions (particularly emergency actions) taken within the health system did not result in the further exacerbation of existing inequities. For example, the agency engaged on a daily basis with Hei Āhuru Mōwai worked closely with clinical colleagues around the country, generated evidence-based guidance that specifically addressed pathways through which inequity could occur, 27 and then regularly monitored differences. 28 To date, as a result of these approaches, we found that with few exceptions, the disruptions caused did not increase inequity in cancer diagnosis and treatment as of the end of 2021.…”
Section: Panel 2: Providing Equity-focused Cancer Control Guidance Du...mentioning
confidence: 99%
“…While these increased numbers may be attributed to better accessibility to diagnosis or increased awareness of cancer (Ministry of Health, 2019), such statistics are highly significant in relation to the population size. Due to the healthcare system's COVID-19 response, there were significant staff shortages in cancer wards (Millar et al, 2021). As a result, some aspects of cancer treatment shifted away from hospital-based care to home-based care with assistance provided by informal cancer carers (Masa et al, 2020).…”
Section: Table Of Contentsmentioning
confidence: 99%
“…Te Aho o Te Kahu, the government's Cancer Control Agency worked with various national organisations and agencies, such as Te Whatu Ora to implement multiple plans in response to This included the diversion of health staff toward the pandemic response, reducing staffing in oncology and other cancer service wards (Millar et al, 2021). March and April 2020 saw a 40% decrease in cancer registrations and initiation of cancer treatment, causing severe backlogs from then on (Gurney et al, 2021).…”
Section: The Covid-19 Pandemic In Aotearoamentioning
confidence: 99%